Surgical Extraction of a Huge Pacemaker Lead Vegetation Causing Infective Endocarditis (Cardiovascular Journal, 2020)
Infections of implantable intracardiac devices such as pacemakers are relatively rare but serious complications. In this paper we report removal of a huge vegetation in RV lead of permanent pacemaker though open surgical approach using extracorporeal circulation which was giving rise to lead endocarditis. A new epicardial lead was placed as the patient was pacemaker dependent. Though the culture of the extracted material didn’t reveal any organism but the patient was improved a lot after operation from both symptomatic (subsidence of fever) & hemodynamic point of view. In follow-up OPD visit she was found to be recovered well without any complication. In conclusion, explantation of the entire pacemaker system is necessary to cure lead endocarditis in addition to appropriate antibiotic therapy.Cardiovasc. j. 2020; 12(2): 162-166